Seasonal changes in the physiological and hormonal aspects of reproduction in the male long-fingered bat, Miniopterus schreibersii (Mammalia : Chiroptera) - Paton, Joy Carol (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1989)
The reproductive cycle of Miniopterus schreibersii is modified as a consequence of a period of torpor/hibernation over the winter months. This bat is one of three genera which employ the reproductive strategy of delayed implantation in which the blastocyst remains free in the uterine lumen during the winter months. Spermatogenesis is initiated in February, with spermiogenesis occuring in March. Copulation, ovulation and fertilization takes place between March and May after which the testes regress and remain in an inactive condition until the following summer. Activity in the accessory gland complex is initiated in March and continues until early June. Plasma testosterone concentrations reach a peak in May, decline over the winter months and reach a second, unexplainable peak in October. Leydig cells are secretorily active in February/early March after which they undergo vacuolation and final degeneration. The question of the life cyle of Leydig cells is addressed and an increase in a certain cell after Leydig cell activity suggests that this cell type may be the precursor of Leydig cells.
Keywords: Bats -- Reproduction